2018
DOI: 10.1002/bit.26809
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess decision support tool for scalable manufacture of extracellular vesicles

Abstract: Newly recognized as natural nanocarriers that deliver biological information between cells, extracellular vesicles (EVs), including exosomes and microvesicles, provide unprecedented therapeutic opportunities. Large-scale and cost-effective manufacturing is imperative for EV products to meet commercial and clinical demands; successful translation requires careful decisions that minimize financial and technological risks. Here, we develop a decision support tool (DST) that computes the most cost-effective techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…A clinical study in a human has shown that 10 10 -10 11 EVs was an effective therapeutic dosage to treat one patient with graft-versus-host disease, with multiple administrations of increasing amounts . This dose was estimated based on therapeutic dosages of transplanted MSCs for similar purposes (~10 -10 8 MSCs); however, other studies indicate that clinical application of EVs may require > 10 14 particles per dose 172 . High concentrations of EVs will require the use of bioreactors for cell culture.…”
Section: -Conclusion and Perspectivesmentioning
confidence: 99%
“…A clinical study in a human has shown that 10 10 -10 11 EVs was an effective therapeutic dosage to treat one patient with graft-versus-host disease, with multiple administrations of increasing amounts . This dose was estimated based on therapeutic dosages of transplanted MSCs for similar purposes (~10 -10 8 MSCs); however, other studies indicate that clinical application of EVs may require > 10 14 particles per dose 172 . High concentrations of EVs will require the use of bioreactors for cell culture.…”
Section: -Conclusion and Perspectivesmentioning
confidence: 99%
“…UC‐based workflows are the most common isolation methods since they enable the recovery of relatively high EV yields at the laboratory scale, especially when compared to alternative methods, such as ultrafiltration (UF), size‐exclusion chromatography (SEC), immunoaffinity capture, and polymer precipitation . However, the implementation of UC on a large scale is challenging because of several reasons: i) it requires large and heavy rotors that demand a consistent amount of electrical power to be operated; ii) being a batch process, it has several dead times that reduce the overall productivity; iii) it often copurifies contaminants; iv) it involves high shear forces, causing aggregation and rupture of EVs; v) the composition of the isolated EV mixture is highly sensitive to a variety of experimental settings such as tube type and rotor type, leading to low consistency of EV mixtures obtained with different ultracentrifuges …”
Section: State‐of‐the‐art Of Ev Productionmentioning
confidence: 99%
“…The large amount of coisolated proteins and lipid impurities demand a further purification step that would negatively impact the processing time and overall yield . Nevertheless, filtration processes were identified as the most versatile and cost‐effective EV isolation methods for scale up …”
Section: Development Of Scalable Ev Purification Processesmentioning
confidence: 99%
See 2 more Smart Citations